Development of a Mindfulness-Based Cognitive Therapy Intervention Package for Patients with Obesity - Saeidiasl, Sahar; Moraveji, Mahtab; Moallem, Masoumeh; hobbi, Mohamad bagher; Manzari Tavakoli, Vahid (Mental Health and Lifestyle Journal, 2026)
The present study was conducted with the aim of developing a mindfulness-based cognitive therapy (MBCT) intervention package for patients with obesity. This study was qualitative in nature and employed a meta-synthesis strategy and research synthesis approach to extract the components of therapeutic packages from credible sources. Two sampling frameworks were considered for data selection: (1) research studies available in electronic databases, including the Noor Specialized Journals Database, Iranian Journal Database, Scientific Information Database (SID) of Jihad Daneshgahi, and Google Scholar search engine; and (2) academic theses archived in the Iranian Scientific Documents and Archives Center. Subsequently, the findings related to selected documents in the relevant thematic domain were synthesized through the processes of open coding, axial coding, and selective coding to develop a new mindfulness-based cognitive therapy intervention package for patients with obesity. The extracted data were summarized and card-indexed, and each element of the therapeutic packages was categorized accordingly. Validation was performed using the Content Validity Index (CVI) and the Content Validity Ratio (CVR) by a panel of 15 experts. Based on the obtained data, the mindfulness-based cognitive therapy model was coded and classified into nine therapeutic themes: (1) conceptualization, (2) awareness of emotions, (3) awareness of real needs, (4) cultivation of self-acceptance, (5) identification of mental wanderings, (6) control of craving and temptation, (7) inner and outer wisdom, (8) mindful and breathing meditation exercises, and (9) mind–body–emotion connection. These results can be utilized in the design and implementation of psychological intervention programs for patients with obesity.